A letter written by the king of Nauarr, to the three estates of Fraunce: containing a most liuely description of the discommodities and dangers of ciuill warre: and a very forcible perswasion to obedience, vnitie, and peace. Together with a breefe declaration vpon the matters happened in Fraunce sithence the 23. day of December. 1588. / Translated out of French, by G.R. [electronic resource] : (1589)
Summary goes here